2014
DOI: 10.4995/wrs.2014.1487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substitution of soybean meal-alfalfa-maize by a combination of field bean or pea with hard wheat bran on digestion and growth performance in rabbits in Algeria

Abstract: The aim of the trial was to study the effects of replacement of a soybean meal-alfalfa-maize based diet by a mixture of field bean (g/kg as fed: 257 crude protein [CP], 139 neutral detergent fibre [NDF]) or pea (g/kg as fed: 203 CP, 122 NDF) combined with hard wheat bran (g/kg as fed: 140 CP, 396 NDF) and without supplementation of synthetic DL-methionine, on diet digestibility, growth and slaughter traits of growing rabbits. Three diets were formulated: a control diet mainly consisting of 15% of soybean meal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…On the other hand, Volek and Marounek (2009) and Volek et al (2013) demonstrated that the addition of 15% WL grain and 5% WL grain hulls to the ration had no effect on the DN. In the study by Lounaouci-Ouyed et al (2014), the GE and TP digestibility coefficients were similar to those in the groups fed diets containing SBM and field bean (Vicia faba L.), while being lower in the group fed feed with 30% pea grain added.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…On the other hand, Volek and Marounek (2009) and Volek et al (2013) demonstrated that the addition of 15% WL grain and 5% WL grain hulls to the ration had no effect on the DN. In the study by Lounaouci-Ouyed et al (2014), the GE and TP digestibility coefficients were similar to those in the groups fed diets containing SBM and field bean (Vicia faba L.), while being lower in the group fed feed with 30% pea grain added.…”
Section: Discussionmentioning
confidence: 65%
“…Bononia et al (2003) are of the opinion that pea meal is a valuable feed, and that it is possible to use it as a soybean substitute. On the other hand, Lounaouci-Ouyed et al (2014) demonstrated that the 30% addition of peas had no effect on growth or feed consumption, but increased the conversion of feed per 1 kg of gain as compared with a feed containing SBM. In other publications on the substitution of SBM with other feeds, the authors explain that the poorer production results may be due to the poorer amino acid composition of the experimental diets (Stein et al 2006;Yang et al 2010;Youssef et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations